Longitudinal associations between perceived programme quality, basic needs support and basic needs satisfaction within youth sport: A person-centred approach. Issue 1 (2nd January 2020) - Bean, Corliss; Solstad, Bård Erlend; Ivarsson, Andreas; Forneris, Tanya
Abstract : Acknowledging the importance of longitudinal data to test process-based psychological theories of motivation is critical. The purpose of this study was to use a person-centred approach to identify unique subgroups (i.e. profiles) of youth athletes based on their level of self-reported programme quality (PQ) and basic needs support mid-way through their sport season and investigate potential differences between the subgroups on their self-reported basic needs satisfaction at the end of the sport season. The current study involved 541 Canadian youth athletes (males n  = 289; females n  = 250; gender-fluid n  = 2) within 52 sport programmes over the course of 18 months. Youth athletes ranged in age from 8 through 19 ( M  = 13.76, SD = 2.61). A latent profile analysis (LPA) in M plus 8.0 was used to carry out the analyses. The LPA revealed three distinct profiles based on youth athletes' levels of self-reported PQ and basic needs support. Specifically, athletes who perceived their sport experience to be of higher quality and supported their basic psychological needs midway through the sport season also reported higher levels of basic needs satisfaction at season end. Results from this study contribute to the field of sport psychology through understanding how basic needs theory contributes to the dimensions of programme quality and by informing recommendations for future coach education on how to satisfy youth athletes' basic psychological needs for autonomy, competence, and relatedness through programme delivery.